Implementation of a conductivity cell electrode as an ion chromatography detector. Issue 9 (9th February 2022) - Kozaki, Daisuke; Tanihata, Souma; Sago, Yuki; Fujiwara, Taku; Mori, Masanobu; Yamamoto, Atushi
Abstract : This technical note illustrates the possibility of using a conductivity cell electrode (CCE) as an ion chromatography (IC) detector to extend the application fields of this analytical technique. Abstract : This technical note illustrates the possibility of using a conductivity cell electrode (CCE) as an ion chromatography (IC) detector to extend the application fields of this analytical technique. A conventional non-suppressed IC system consists of an eluent delivery pump, a separation column, column oven, and conductivity detector (CD). In this study, the conventional CD, which is one of the expensive parts of the instrument, is replaced with a relatively inexpensive CCE, leading to comparable peak resolution, detection sensitivity, and relative standard deviation. The separation effectiveness was retained and the developed IC-CCE system was successfully applied to the simultaneous separation of inorganic anions (SO4 2−, Cl −, and NO3 − ) and cations (Na +, NH4 +, K +, Mg 2+, and Ca 2+ ) in three natural mineral water samples, with good accordance between the monitored values obtained using the CCE and CD. The commercially available CCE is potentially suitable for application as an IC detector for monitoring ionic components with overall IC cost reduction.